−4p+(−6p)
Answer:
- 10p
Step-by-step explanation:
We know that,
( - ) × ( - ) = ( + )
( - ) × ( + ) = ( - )
( + ) × ( + ) = ( + )
Accordingly, let us solve the above expression.
- 4p + ( - 6p )
Solve the brackets.
- 4p - 6p
Combine like terms.
- 10p
Answer: - 10p
Step-by-step explanation A common technique for simplifying algebraic expressions. When combining like terms, such as 2x and 3x, we add their coefficients. For example, 2x + 3x = (2+3)x = 5x.
Answer:
12y +16yi
Step-by-step explanation:
The thing about complex numbers is that you can treat them as binomials and use all of the things you know about multiplying and factoring polynomials.
Here, we assume you have ...
(5 +2yi)(4 -3i) -(5 -2yi)(4 -3i)
The factor (4 -3i) can be factored out, so you have ...
= ((5 +2yi) -(5 -2yi))(4 -3i)
= (4yi)(4 -3i)
= 16yi -12yi²
At this point, the definition of i comes into play, and you replace i² with -1.
= 12y +16yi
Real numbers are all irrational and rational numbers. These are all the numbers on the number line that represent a quantity of some sort.
–18
B.
–6
C.
6
D.
18
We could have 9 ways to pick the leader x 8 ways to pick the second place rider x 7 ways to pick the third place rider, etc.
So
9 x 8 x 7 x .....x 3 x 2 x 1 = 9! = 362880 ways to arrange them